Influence of daily life and health profile in subtle cognitive decline of women residing in Spanish religious communities: DeCo religious orders study - Lopez de Coca, Teresa; Moreno, Lucrecia; Pardo, Juan; Pérez-Tur, Jordi; Ramos, Hernán; Villagrasa, Victoria (Frontiers in Public Health, 2024)
Background Prior to the onset of dementia, individuals commonly undergo a phase marked by subtle cognitive changes, known as subtle cognitive decline. Recognizing these early cognitive alterations is crucial, as they can serve as indicators of an impending decline in cognitive function, warranting timely intervention and support. Objectives To determine the incidence of subtle cognitive decline in a population of Spanish women and establish the relationship with possible protective and/or risk factors such as cognitive reserve, cardiovascular risk factors, medication consumption and psychosocial factors. Design and participants This is a cross-sectional observational study with women from the general population and a more homogeneous population composed of nuns from the Valencian region (Spain). Measurements A validated questionnaire was used including lifestyle variables, chronic illnesses, level of education and pharmacological treatments. Three validated subtle cognitive decline screening tests with varying levels of sensitivity and specificity were used: Memory Impairment Screening, Pfeiffer’s Short Portable Mental State Questionnaire, and Semantic Verbal Fluency. Results Our results suggest that nuns may have a significantly reduced risk of cognitive decline compared to the general population (20.67% in nuns vs. 36.63% in the general population). This lower risk for subtle cognitive decline in nuns may be partly attributed to their higher cognitive reserve and long-time engagement in intellectually stimulating activities. Additionally, nuns tend to adopt healthy lifestyles, they are not isolated because they live in community and obtained lower scores for risk factors such as depression, anticholinergic burden, and benzodiazepine consumption. Conclusion A healthy lifestyle combined with intellectually stimulating activities is related with preserved cognitive function.